Effect of sinusoidal electromagnetic field pretreatment on maize seed borne fungi - Devi, I Swarnalatha; Parimala, K; Bharathi, V; Leelapriya, T (Indian Journal of Plant Protection, 2020)
The role of magnetic fields and their influence on agricultural field crops are still insufficiently understood but actively studied. Pulsed magnetic field treatment (PMF) is one physical treatment where exposure of seeds to varying pulsating magnetic fields improves the seed coat membrane integrity, vigour, reduces the cellular leakage and electrical conductivity. A study on pulsed magnetic field on maize inbred, BML-6 was taken to conduct experiment during Kharif, 2012-13 at Seed Research and Technology Centre, Hyderabad. Seeds of maize were exposed to pulsed magnetic fields of varying frequencies of 1 Hz, 10 Hz, 50 Hz and 100 Hz with intensity of 1500nT, sine wave for a period of 5 hrs per day for 15 days. These treated seeds were sown and after maturity cobs were harvested from different treatments separately to assess the effect of pulsed magnetic field on seed quality parameters and seed health assay. Significant increase in the rate of germination, seedling length was observed in all the treatments when compared to control. Seeds harvested from the treatments of 50 Hz and 100 Hz proved to have maximum vigour index of 2665 and 2576, respectively. While the treatment with 1 Hz and 10 Hz displayed the highest fungal infestation (22.0 to 27.6 %) with the smallest share of germinated seeds ranging from 62 to 76%. The PMF treated seeds with 50 Hz and 100 Hz exhibited significant differences for the frequency of occurrence of fungi of different genera and species when compared to 1 Hz and 10 Hz. The frequency of occurrence of fungi was maximum with minimum frequency of magnetic field. The frequency of recovery of fungi was maximum from seeds with minimum dose of exposure of magnetic field and minimum with maximum frequency. Nine fungal species were isolated from treated and untreated seeds of maize by blotter method. As per the magnetic field, the growth of colonies was decreased by 10 % using this flux density. The results indicate that the higher magnetic field of 50 Hz and 100 Hz was found to be good for the control of storage fungi in maize seeds.